Grading scale in physical education class - abdsalem, Salima (sports creativity, 2025)
The educational assessment in general, and the evaluation of students' achievement and performance in particular, is witnessing rapid developments, innovative renewals, and fundamental transformations in measurement and evaluation methodologies and their frameworks, as well as a qualitative shift in its methods, tools, techniques, and field practices. These developments have contributed to comprehensive educational changes in various components of the educational system. This is evident in the reform movements of educational assessment systems in educational institutions in many countries around the world, especially developed countries, over the past two decades. It is also reflected in the new trends in research and studies on measurement and evaluation, which the specialized literature in this field has been abundant with recently. Therefore, assessment is considered a necessary process in the field of education. If we find methods and arrangements for evaluating regular educational subjects through homework and tests presented to students in the form of exercises or essays, text reviews, or scientific knowledge, physical education does not use the same methods for assessment. Physical education's intended goals are more educational than instructional; therefore, it is necessary to use methods that allow us to understand the level of a student's physical, motor, and social development students